Results from an international interlaboratory study on light‐ and elevated temperature‐induced degradation in solar modules. (5th May 2022) - Karas, Joseph; Repins, Ingrid; Berger, Karl A.; Kubicek, Bernhard; Jiang, Fangdan; Zhang, Daqi; Jaubert, Jean‐Nicolas; Cueli, Ana Belén; Sample, Tony; Jaeckel, Bengt; Pander, Matthias; Fokuhl, Esther; et al.
Abstract: This paper reports the results of an international interlaboratory comparison study on light‐ and elevated temperature‐induced degradation (LETID) on crystalline silicon photovoltaic (PV) modules. A large global network of PV module manufacturers and PV testing laboratories collaborated to design a protocol for LETID detection and screen a large and diverse set of prototype modules for LETID. Results across labs indicate the reproducibility of LETID testing is likely within ±1% of maximum power (PMP ). In intentionally engineered LETID‐sensitive modules, mean degradation after the prescribed detection stress is roughly 6% PMP . In other module types the LETID sensitivity is smaller, and in some we observe essentially negligible degradation attributable to LETID. In LETID‐sensitive modules, both open‐circuit voltage (VOC ) and short‐circuit current (ISC ) degrade by a roughly similar magnitude. We observe, as do previous studies, that LETID affects each cell in a module differently. An investigation of the potential mismatch losses caused by nonuniform LETID degradation found that mismatch loss is insignificant compared to the estimated loss of cell ISC, which drives loss of module ISC . Overall, this work has helped inform the creation of a forthcoming standard technical specification for LETID testing of PV modules, IEC TS 63342 ED1, and should aid in the interpretation of results from that and other LETID tests. Abstract : A global network of PV manufacturers and laboratories designed a test for LETID detection in PV modules and screened a diverse set of modules for LETID. Results across labs indicate the reproducibility is likely within ±1% of maximum power (PMP ), and that power loss is driven by losses in both voltage and current. Overall, this work should aid in the interpretation of results from a forthcoming standard technical specification for LETID testing and other LETID tests.